Priznanje pravne subjektivitete umetni inteligenci za namene odškodninske odgovornosti - Renko, Jernej (Pravni letopis, 2024)
The article examines the question of granting legal personhood to artificial intelligence (AI) in the context of liability for damages. The author analyzes the concept of autonomous AI systems and their key features, such as autonomy and learning capability. The risks posed by these systems are highlighted, particularly unpredictability and difficulties in determining the subject of tort liability. The article introduces the idea of an »electronic person« as a possible solution for attributing responsibility to AI systems. The author addresses philosophical concerns regarding granting legal personhood to AI, including ontological, epistemological, and ethical questions. Despite these concerns, he advocates for a pragmatic approach, similar to that used in recognizing legal personhood for corporations. The main advantages of recognizing AI legal personhood are cited as facilitating the proof of causality in damage cases and potential economic efficiency. The article concludes with a discussion on implementation possibilities, such as providing minimum capital or introducing special liability insurance for AI systems, and warns of potential limitations of these solutions.
Keywords: artificial intelligence; autonomous systems; avtonomni sistemi; deliktno pravo; electronic person; elektronska oseba; ethical issues; etična vprašanja; legal personhood; liability for damages; liability insurance; minimalni kapital; minimum capital; odškodninska odgovornost; pravna subjektiviteta; tort law; Umetna inteligenca; zavarovanje odgovornosti